ANALYSIS OF THE FUNCTIONS AND ROLES OF THE STATE CIVIL APPARATUS OF THE SECRETARIAT OF THE DPR OF CENTRAL PAPUA - Allo, Viktor Payung; Roreng, Petrus Peleng (Journal of Entrepreneur, Business and Management, 2025)
This study analyzes the functions and roles of ASN of the Trial, Report, and Publication Sub-Division of the Secretariat of the Central Papua DPR in supporting the duties and functions of the Central Papua DPR. Using a qualitative approach, data was collected through in-depth interviews, observations, and document analysis. The results of the study indicate that ASN has a crucial role in the administration of trials, preparation of minutes, and publication of the activities of the Central Papua DPR. However, there are several obstacles, such as limited human resources, lack of optimization of information technology, and less than optimal coordination between ASN and members of the Central Papua DPR. Therefore, this study recommends increasing the capacity of ASN through training, optimization of digital information systems, and improving internal coordination in order to increase the effectiveness of work and transparency of publications of the Central Papua DPR. Keywords: Role of ASN, Secretariat of the Central Papua DPR, trial administration, parliamentary publications